Hemodynamic Changes during a Deep Inspiration Maneuver Predict Fluid Responsiveness in Spontaneously Breathing Patients. (13th December 2011) - Préau, Sébastien; Dewavrin, Florent; Soland, Vincent; Bortolotti, Perrine; Colling, Delphine; Chagnon, Jean-luc; Durocher, Alain; Saulnier, Fabienne
Abstract : Objective . We hypothesized that the hemodynamic response to a deep inspiration maneuver (DIM) indicates fluid responsiveness in spontaneously breathing (SB) patients. Design . Prospective study. Setting . ICU of a general hospital. Patients . Consecutive nonintubated patients without mechanical ventilation, considered for volume expansion (VE). Intervention . We assessed hemodynamic status at baseline and after VE. Measurements and Main Results . We measured radial pulse pressure (PP) using an arterial catheter and peak velocity of femoral artery flow (VF) using continuous Doppler. Changes in PP and VF induced by a DIM (Δ PPdim and Δ VFdim) were calculated in 23 patients. Δ PPdim and Δ VFdim ≥12% predicted responders to VE with sensitivity of 90% and specificity of 100%. Conclusions . In a restricted population of SB patients with severe sepsis or acute pancreatitis, Δ PPdim and Δ VFdim are accurate indices for predicting fluid responsiveness. These results should be confirmed in a larger population before validating their use in current practice.